Physiological responses of Indigofera zollingeriana, a feed plant at different levels of drought stress and trimming interval - I, Herdiawan; L, Abdullah; ., Yoki; PDMH, Karti; N, Hidayati (Indonesian Animal Sciences Society, 2013)
The objectives of this experiment were to evaluate the effect of drought stress and trimming intervals on physiological responses of Indigofera zollingeriana. The experiment was arranged in a completely randomized design (CRD), 3x3 factorial and each treatment had four replications. The first factor consisted of 3 level of drought stress i.e: 100% field capacity (FC) (as a control), 50% FC, and 25% FC.Â The second factor was comprised of 3 trimming intervals, those were at 60, 90 and 120 days. The observed variables were leaf water potential, relative water content, proline, and water soluble carbohydrate (WSC) concentrations. Data were analyzed by ANOVA and differences between treatments were tested by LSD. The results showed that there were no interaction (P<0,05) between drought stress and trimming interval on all observed variables. Drought stress treatment significantly (P<0,05) decreased leaf water potensial and relative water content, whereas proline, and water soluble carbohydrate (WSC) contents increased. Trimming interval significantly (P < 0.05) on leaf water potensial, and water soluble carbohydrate, whereas the relative water content and proline content were not significantly. Key Words: Indigofera zollingeriana, Drought stress, Trimming interval, Physiologycal response